Gender Inequality in Tri Utami’s Novel Entitled Dunia Padmini - Sri Lestari; Arif Nugroho (POETIKA, 2022)
The present study examines the issue of women’s internal struggle in response to patriarchal culture and gender inequality portrayed in Tri Utami’s novel entitled Dunia Padmini. Drawing on textual analysis, this study describes empirical facts and evidence related to gender inequality in the novel. The analysis results demonstrate that the financial dependence and subordination of women are forms of gender inequality. This is also supported by social constructions that give negative stereotypes to the role of women as second-class citizens. This construction has not changed much even when women have juggled dual roles (domestic and public). The results of this study contribute to literature enrichment regarding the issue of gender equality based on socio-feminism theory, particularly on strengthening the roles and rights of women in social life, and how they get their rights in society.